2021
DOI: 10.21037/tcr-20-3333
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular targeting of STIP1 inhibits human cancer cell line growth

Abstract: Background: Extracellular and cell-surface molecules remain the most common druggable cancer targets.However, intracellular therapeutic modalities are gaining momentum. The overexpression of stress-induced phosphoprotein 1 (STIP1), an adaptor protein that coordinates the functions of different chaperones in protein folding, has been reported in several solid malignancies. Here, we investigated the effects of intracellular STIP1 inhibition, attained either through the HEPES-mediated cytosolic delivery of anti-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is actively involved in transcription regulation, cell cycle regulation, signal transduction, protein folding, and cell division [19] . Previous studies have consistently demonstrated that elevated expression of STIP1 is commonly associated with an unfavorable prognosis in patients with various malignant tumors, including hepatocellular carcinoma, pancreatic cancer, colorectal cancer, gastric cancer, and ovarian cancer [20] . However, the diagnostic value of STIP1 in HCC and ANHC has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is actively involved in transcription regulation, cell cycle regulation, signal transduction, protein folding, and cell division [19] . Previous studies have consistently demonstrated that elevated expression of STIP1 is commonly associated with an unfavorable prognosis in patients with various malignant tumors, including hepatocellular carcinoma, pancreatic cancer, colorectal cancer, gastric cancer, and ovarian cancer [20] . However, the diagnostic value of STIP1 in HCC and ANHC has not been reported.…”
Section: Introductionmentioning
confidence: 99%